Effects of time of day on the performance of soccer-specific motor skills - Reilly, T.; Farrelly, K.; Edwards, B.; Waterhouse, J. (Journal of Sports Sciences, 2004)
The study investigated the influence of the time of day on the motor skills related to soccer which is essential to know because football games take place at different times of day.